Geochemistry and Petrogenesis of Carboniferous volcanic rocks, NW Marand: Evidence for interacontinental rift Magmatism) - Zahra Badrzadeh; Mehraj Aghazadeh; Sahar Fathi (پترولوژی, 2020)
The studied volcanic-sedimentary sequence located at the East-Azarbaijan province, north Marand and in the Central Iranian structural zone. The studied sequence composed of alternative sandstone, shale, conglomerate, limestone, felsic volcaniclastics, alkalibasalt and rhyolite which outcropped below the Permian sedimentary sequence and on the Devonian sedimentary rocks. Magmatism in the area has a bimodal magmatic characteristic and the basaltic rocks have alkaline affinity. They are characterized by enrichment of LILE over HFSE and show significant OIB-type trace element signatures. On the basis of trace element data, the basic rocks generated by low degree partial melting of garnet-spinel lherzolite mantle source with ocean island basalt characteristics, which fractionated en route to the surface. On the basis of geological and major and trace elements data, the felsic rocks are comparable to A-type granitoids and their trace element ratios are very close to determinate bulk continental crust composition which indicate their crustal origin. The felsic rocks were originated by the dehydration melting of a tonalite or granodiorite source with a plagioclase rich residual assemblage. The Carboniferous bimodal volcanism were induced by continental rifting and asthenospheric upwelling during early phases of Neotethys opening.